Mode 1 or mode 2? "Small tools" in the technical variability of the European Lower Palaeolithic: The site of Ficoncella (Tarquinia, Lazio, central Italy). (30th January 2016) - Aureli, Daniele; Rocca, Roxane; Lemorini, Cristina; Modesti, Valerio; Scaramucci, Sem; Milli, Salvatore; Giaccio, Biagio; Marano, Federica; Palombo, Maria Rita; Contardi, Antonio
Abstract: The site of Ficoncella, in northern Latium (Italy), represents a great opportunity to investigate the modalities of a short occupation in a fluvial context during Lower Palaeolithic. From the results of radiometric dating, geological study and bio-chronological analyses, it emerged that the human occupation at the site, an ancient riverbank, occurred 0.5 Ma (MIS 13). This period can be considered as a key moment in the Lower Palaeolithic, with the first Acheulean, or mode 2 sites in Europe. The lithic assemblage of Ficoncella, without handaxes, is characterized by an overall small tool size, representing a very original reduction sequence and tool management. In order to investigate the human behaviour characterizing the site, we analyse the lithic industries, using a classical technological analysis, combined with a techno-functional approach and a use-wear analysis. The study of the lithic assemblage of Ficoncella may contribute to renew our image of the lithic industries without handaxes, too often ignored.